Ordinary Wisdom - Healy, Eloise Klein (Book collections on Project MUSE., 2013)
In writing this series of poems, Eloise Klein Healy rediscovered allowing constellations or clusters of associations to gather and from these configurations to extrapolate, to generate another layer of clusters, images, meanings. Her immediate sense was to write a series of poems using these ideograms as "initiators." These pieces came together.